POD-based reduced order model of a thermoacoustic heat engine - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2014)
In this study, numerical simulation of a thermo-acoustic heat engine is performed and a reduced order model of the system based on the Proper Orthogonal Decomposition method is obtained. The governing equations are solved with a finite volume-based solver. The reduced order model is constructed using the snapshots when the system reaches the limit cycle. A quadratic polynomial type ODE system with 11-modes is constructed from the Galerkin projection for the high fidelity CFD computations of the coupled thermo-acoustic system. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: Thermo-acoustic Heat engine; Proper Orthogonal Decomposition; Computational fluid dynamics